Les systèmes sacrificiels de l'Ancien Testament : formes et fonctions du culte sacrificiel à Yhwh - Marx, Alfred. (Supplements to Vetus Testamentum,, 2005)
The present study is an attempt to decode the sacrificial system of ancient Israel, to understand how the different kinds of sacrifice are related, the choice of the sacrificial materials, and the shape of their ritual. Special attention is given to the social function of sacrifice. Starting from a comparison between the isolated data and the systems of P, the Chronist and Ezekiel, the study stresses the specificity of each system, and tries to point out the distinctive features of Israel's sacrificial cult. The concluding chapter sketches the evolution of the sacrificial cult. An exhaustive index of textual references offers an overview of all Old Testament passages relating to sacrifice.